Legal Analysis of Optimizing Eradication of Narcotics Trafficking Crimes Through Digital Media in the Central Java Regional Police Area - Wulansari, Restu Tri; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The crime of drug trafficking through digital media is a cyber crime that has an extraordinary impact and has a wide scope. This thesis research aims to analyze and determine the optimization of the eradication of drug trafficking through digital media in the Central Java Regional Police Area at this time and to analyze and determine the obstacles and solutions in realizing the optimization of the eradication of drug trafficking through digital media in the Central Java Regional Police Area. The research method used in this thesis is non-doctrinal research, namely research that examines legal issues from both juridical and empirical dimensions. The results of the research conducted show that the optimization of the eradication of narcotics trafficking crimes through digital media in the Central Java Regional Police area has not yet been realized, according to an explanation from Senior Commissioner of Police Anwar Nasir as Director of Drug Investigation of the Central Java Regional Police, there are at least 47 suspicious accounts and forum sites in narcotics trafficking cases, but only 5 cases can be investigated with certainty throughout 2024. The main obstacle in the problem of the less than optimal eradication of narcotics trafficking digitally in the Central Java Regional Police area is that the Republic of Indonesia Law Number 35 of 2009 concerning Narcotics does not clearly regulate the digital circulation of narcotics where the modus operandi is cyber crime, then the meaning of acts that deviate from morality in Article 27 paragraph (1) of Law No. 19 of 2016 concerning ITE does not refer to the digital circulation of narcotics specifically. Due to the problem of unclear regulations regarding the digital distribution of narcotics, it has an impact on uncertainty regarding the elements of the act for perpetrators of digital drug distribution. This has resulted in aspects of the requirements for sentencing perpetrators of digital drug distribution, considering that the element of cyber crime as a specificity in the crime of digital drug distribution is not yet clear. This also has an impact on the lack of regulation of special sentencing guidelines based on the impact of damage or the consequences of criminal acts for perpetrators of digital drug distribution crimes. The solution that can be done is to specifically regulate the elements of the act as a requirement for sentencing related to the crime of drug distribution as a cyber crime. Formulate a maximum penalty with an aggravation in the form of the death penalty for perpetrators of digital drug distribution considering that the impact of digital drug distribution. The level of damage caused to national stability is greater. The government needs to enforce the prohibition of site content and internet content related to drug distribution for those who own internet technology as a place for unlimited social interaction. The suggestion from the results of this thesis study is that the government needs to specifically regulate the elements of the act as a requirement for criminal punishment related to the crime of drug trafficking as a cyber crime. For law enforcers, there needs to be education and provision of knowledge and expertise as well as experience for human resources.